Monster hunter guardian - Correia, Larry; Hoyt, Sarah A. (Correia, Larry. Monster hunter series., 2020)
When Owen Pitt and the rest of the Monster Hunter International crew are called away to mount a months-long rescue mission in a monster-infested nightmare dimension, Julie Shackleford--Owen's wife and descendant of MHI founder Bubba Shackelford--is left behind. Her task: hold down the fort and take care of her new baby son Ray. Julie's devoted to the little guy, but the slow pace of office work and maternity leave are starting to get to her. But when a routine field call brings her face-to-face with an unspeakable evil calling itself Brother Death, she'll get more excitement than she ever hoped for. Julie is the Guardian of a powerful ancient artifact known as the Kamaresh Yar, and Brother Death wants it. In the wrong hands, it could destroy reality as we know it. Julie would die before giving it up. Then Ray goes missing, taken by Brother Death. The price for his safe return: the Kamaresh Yar. If Julie doesn't hand over the artifact it means death--or worse--for baby Ray. With no other choice left to her, Julie agrees to Brother Death's demands. But when you're dealing with an ancient evil, the devil is in the details. To reclaim her son, Julie Shackleford will have to fight her way through necromantic death cults, child-stealing monsters, and worse. And she'll have to do it all before Brother Death can unleash the Kamaresh Yar. It's one woman against an army of monsters. But Julie Shackelford is no ordinary woman--she's one tough mother!